Recombination of many-particle states in InAs self-organized quantum dots - Yuan, Z; Foo, E; Ryan, J; Mowbray, D; Skolnick, MS; Hopkinson, M (2001)
Strong many-body effects have been observed in the time-resolved photoluminescence spectroscopy of self-organized InAs/GaAs quantum dots. Our results show that the effects generate a considerable bandgap renormalization, being 28 meV at a dot occupancy of 20 electron-hole pairs for the lowest transition. Tt is also found that many-particle state scattering gives rise to a large homogeneous broadening of the photoluminescence peak, from which we estimate the intradot relaxation time to be 300 B. The fast intradot relaxation is supported by time-resolved measurements with direct excitation.